Pseudo Randomized Search Strategy (PRSS*) of the ambiguity function mapping - Hassan, Azmi (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1998)
A technique has been developed for reliably resolving the GPS carrier phase ambiguity over a medium length baseline. A combination between three methods of optimization, global random search and ambiguity function mapping produced an efficient search algorithm what the author called the Pseudo Randomized Search Strategy (PRSS). The PRSS is a adaptive search technique that can learned high performance knowledge structures in reactive environments that provide information in the form of a objective function. What makes this search is efficient is that the objective function, where all the GPS measurement resides are evaluated periodically to guide the search to a global optimum. Numerical results shows that, in all the test cases, no more than 5% search of the total search space was conducted to determine the correct set of ambiguities. This result shows that the size of the search window does not play an important role in determining the efficiency of the search and therefore suitable for the on-the fly ambiguity resolution of a single frequen9Y CIA code receiver.